Investigation of Vickers Hardness in Hardened Scrap Automotive Spring Steel - A. E. Heka; M. Hasbi (Asian Journal of Mechanical Engineering, 2025)
The objective of this study is to investigate the effect of hardening temperature on the surface hardness of high carbon steel. The research was conducted experimentally in a laboratory setting using descriptive statistical analysis. The material used was high carbon steel with a carbon content of 0.465%. Three hardened test samples were subjected to Vickers hardness testing, with five indentations measured on the upper, middle, and lower sections of each sample. One additional sample was left untreated as a control. The hardening process involved heating the samples to varying austenitizing temperatures of 600°C, 700°C, and 800°C, followed by quenching in water. The findings of this study aim to reveal the hardness characteristics of recycled leaf spring steel after undergoing different hardening treatments.